An experimental study on the ballistic behavior of AA 7017 alloy plates at room temperature and at -40°C temperature - Jena P.K.; Siva Kumar K.; Mandal R.K.; Singh A.K. (My University, 2025)
This investigation describes and presents the analysis of the experimental results on the penetration of AA 7017 plates by high hardness steel projectiles at a velocity of 850±15 m/s at room temperature and at -40°C. From the ballistic testing experiments it is observed that the AA 7017 plates display better ballistic resistance at -40°C than at room temperature. The ballistic testing results have been interpreted in terms of mechanical properties of the material at room temperature and at -40°C. The damage patterns of the plates after ballistic testing have been studied in order to understand the change in ballistic behavior of the material. © 2018 Elsevier Ltd. All rights reserved.